Systematization of the e-commerce experience in agricultural companies in Costa Rica - Villalobos Moya, Keylor (2023)
This paper presents the e-commerce experience resulting from supporting the commercialization of agricultural products in Costa Rica as part of the UNAPROPYMES project: Incubation/acceleration of e-commerce websites for Costa Rican SMEs (Small and Medium-Sized Enterprises) in response to the COVID-19 pandemic. Five e-commerce websites were developed in this project for marketing agricultural products: three related to organized groups of small producers and two to individual agricultural entrepreneurs. This was done with the purpose of providing these producers with an alternative way to face the marketing problems presented during the COVID-19 pandemic, using the joint design (co-design) of their e-commerce websites. Of these five prototypes (resulting from the incubation stage), only three have been implemented (resulting from the acceleration stage); however, one of them had to be disabled at the request of the organization in charge. Based on this experience, recommendations are given to develop e-commerce websites for agricultural organizations in Costa Rica.